Analysis of Cumulative Fluid Balance Impact on the Stability of Gastrointestinal Tract Anastomosis - Örhalmi, Julius; Turek, Zdeněk; Dolejš, Josef; Páral, Jiří; Malý, Ondřej; Čečka, Filip (The Indian journal of surgery, 2022)
Anastomotic leakage is a serious postoperative complication following a low anterior resection of rectum. Current research in colorectal surgery focuses on searching for techniques which could minimize the risk of leakage. The main objective of this study was to evaluate the impact of cumulative fluid balance on microcirculatory changes at the anastomotic site.This experimental study used 15 domestic pigs; all of the animals underwent rectal resection. Then the animals were divided into three groups and received IV crystalloids at various rates, i.e. 5 ml/kg/h; 10 ml/kg/h; and 20 ml/kg/h. Large bowel micro-perfusion was measured using laser Doppler flowmetry during and following the surgical procedure.The experiments were successfully performed in all 15 cases. No animal died during the procedure or during the follow-up. We found no differences in micro-perfusion of the bowel between the experimental groups during the surgical procedure and during the follow-up period after the surgery. A significant decrease in micro-perfusion was observed after the transection of the inferior mesenteric artery in all the groups; again, no differences between the groups were observed.We did not confirm the original hypothesis that excessive load of IV crystalloids during the surgery would have a negative effect on bowel micro-perfusion and thus a negative effect on the healing of the anastomosis. However, laser Doppler flowmetry was found to have high accuracy in measuring tissue microcirculation and has the potential to be used in clinical practice.
Keywords: Low anterior resection; Anastomotic leakage; Laser Doppler flowmetry; Blood flow